Bacteriophages to Control Campylobacter in Commercially Farmed Broiler Chickens, in Australia - Chinivasagam, Helene N.; Estella, Wiyada; Maddock, Lance; Mayer, David G.; Weyand, Caitlin; Connerton, Phillippa L.; Connerton, Ian F. (Frontiers in Microbiology, 2020)
This study describes the development and use of bacteriophage cocktails to control Campylobacter in broiler chickens, in a commercial setting, in Queensland Australia, following the birds from farm to the processing plant. The components of the bacteriophage cocktails were selected to be effective against the maximum number of C. jejuni and C. coli isolates encountered on SE Queensland farms. Farms were identified that had suitable Campylobacter target populations and phage were undetectable one week prior to the intended treatment. Cocktails of phages were administered at 47 days of age. Groups of study birds were slaughtered the following day, on-farm, at the end of flock transport to the plant, and at processing (approximately 28 h post-treatment). On Farm A, the phage treatment significantly reduced Campylobacter levels in the ceca at the farm in the range of 1 – 3 log10 CFU/g (p = 0.007), compared to mock treated controls. However, individual birds sampled on farm (1/10) or following transport (2/10) exhibited high cecal Campylobacter counts with low phage titers, suggesting that treatment periods >24 h may be required to ensure phage replication for effective biocontrol in vivo. At the time of the trial the control birds in Farm B were phage positive despite having been negative one week earlier. There was no significant difference in the cecal Campylobacter counts between the treatment and control groups following treatment but a fall of 1.7 log10 CFU/g was observed from that determined from birds collected the previous week (p = 0.0004). Campylobacter isolates from both farms retained sensitivity to the treatment phages. These trials demonstrated bacteriophages sourced from Queensland farms have the potential to reduce intestinal Campylobacter levels in market ready broiler chickens.